Are COVID‐19 Layoffs a Red‐Flag on Innovation?. (30th August 2020) - Cervantes, Leticia
Abstract : Over centuries we've seen that each economic and political hurdle we've encountered has kindled innovation and progress. During tough times such as these, some companies lay off their creative staff—others view the situation as an opportunity for innovation.